FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEHAMILAN RESIKO TINGGI DI PUSKESMAS CIBATU KABUPATEN BEKASI PROVINSI JAWA BARAT TAHUN 2017 - Nurmawati Nurmawati (Jurnal Ilmu dan Budaya, 2017)
Maternal Mortality Rate (AKI) by Indonesia Demographic and Health Survey in 2017,shows an AKI of 359 / 100,000 live births. Efforts to reduce MMR basically refers to strategic intervention Four Pillars of Save Motherhood, where one of them is access to pregnancy screening services whose quality still needs to be improved continuously. This study aims to determine Factors Associated With High Risk in Pregnant Women In Puskesmas Cibatu Bekasi Regency of West Java Province in 2017. The study was conducted using Cross Sectional approach. The population in this study is pregnant women, the sample used is the total sampling of 55 pregnant women. The data collected in this research is using primary data with questionnaire. The research analysis was done by univariate and bivariate technique using Chi Square Test. The result of the research was obtained by high knowledge pregnant women as much as 36 respondents (65,5%), pregnant mother earn <UMR counted 35 people (63,6%), pregnant mother who get family support as much as 33 person (60,0%), pregnant mother Did not get information about high risk knowledge from health workers as many as 31 people (56.4%) and pregnant women are not high risk that is as much as 29 respondents (52,7%). Conclusion There is a significant relationship between knowledge variables (ρ Value = 0,000: OR = 25,500), health worker (ρ Value = 0,000: OR = 20,125), education (ρ Value = 0,022: OR = 0,224) and family support (ρ Value = 0,000: OR = 0.071). There was no significant association between income (ρ Value = 0,000: OR = 25,500) at high risk for pregnant women. Suggestions for officers, make plans for the formation of pregnant women's classes and cooperate with posyandu cadres and community leaders to increase the knowledge of pregnant women.